(untitled) (Journal of Economic Research & Business Administration, 2018)
In this study the information was given regarding Kano’s Model and a case study was conducted for university students. Kano’s Model was applied for Akhmet Yassawi University students and it was questioned what they thought were important quality requirements in higher education, the degree of their importance and how they evaluated their own institutions with respect to the quality requirements. The purpose of this study is to determine the student requirements regarding the quality of the undergraduate programs of Tourism Management and Finance in Akhmet Yassawi University and to analyze the student satisfaction and dissatisfaction and their majority roles in determining and improving the quality of the programs. To achieve this object, firstly Kano’s Survey was applied to 116 students and the student requirements relating to the education were uncovered by focusing on group work. Secondly, these requirements were classified by Kano Evaluation Table. Thus, the quality requirements divided into four categories: must-be, one-dimensional, attractive and indifferent. Finally, the values of satisfaction and dissatisfaction were calculated and the roles of these requirements in increasing and decreasing student satisfaction and dissatisfaction were identified clearly